Using perturbation theory to detect the falsification of the digital image - Кобозева, А. А. (Problems of Informatization and Control, 2008)
A new approach to the problem of detecting falsification of the digital image , based on the analysis of perturbations of singular values ​​( eigenvalues ​​) matrix blocks of the image. The approach makes it possible to localize the area of ​​unauthorized changes to the original image